KUALITAS PELAYANAN PUBLIK DI KANTOR KECAMATAN BILUHU - Fitroy Ishak (Publik : (Jurnal Ilmu Administrasi), 2015)
Service quality is not only become the necesity and demands of the user society service, but also the demands of governance be a good governance. This research aimed to know the quality of E-KTP service in sub-district Biluhu Gorontalo regency. This research used a qualitative method. Decision informant/respondent is doing by purposive and snow ball. The data were collected through observation nonparticipant, in-depth interviews, and a review of documents. Analysis of the data is using reduction of data, data presentation, and conclusion and verification. The results showed that the E-KTP service in sub-district Biluhu Gorontalo regency has require the tangible aspects, namely matters relating to physical Visibility, such as equipment and facilities have adequate services; but have not been able to requare the elements of reliability, the service provided is likely to be inaccurate; has not been able to requare the elements of responsiveness, the officer tended slowly to respond the society complaints; has not been able to requare the elements of assurance, that the existing services do not provide assurance that expected by society; and also not been able to requare the elements of empathy, that has the differences in the treatment of servicing and even more the society feel that the officers more priority the other case compared the services. Thus, it can be know that the E-KTP service in in sub-district Biluhu Gorontalo regency not yet qualty.